Development of a Solid Self‐Emulsification Delivery System for the Oral Delivery of Astaxanthin. Issue 5 (5th April 2019) - Mao, Xinyu; Sun, Rui; Tian, Yuan; Wang, Dantong; Ma, Yudi; Wang, Qiang; Huang, Juan; Xia, Qiang
Abstract : In the present study, a solid self‐emulsification delivery system (S‐SEDS) is developed to improve the bioavailability of astaxanthin (ASX). The pseudo ternary phase diagram method is used to screen the optimum composition of liquid self‐emulsification delivery system (SEDS). This liquid system is converted into solid state using the solid absorbent carrier by simple physical mixing. Through the analysis of powder flowability and adsorption capacity, silicon dioxide and anhydrous calcium hydrogen phosphate are selected as solid carriers of the liquid self‐emulsification system. Results of Fourier transform infrared spectroscopy (FTIR) and X‐ray diffraction (XRD) indicate that astaxanthin is encapsulated in these solid carriers. In the in vitro dissolution study, sustained release of astaxanthin from two different ASX‐SEDS (prepared with silicon dioxide and anhydrous calcium hydrogen phosphate) is obtained and the cumulative release is correspondingly 51.06 ± 0.98 and 49.97 ± 0.87% within 2 h. A delayed pattern of absorbed ASX‐SEDS is observed in the study with anhydrous calcium hydrogen phosphate compared to the counterpart with silicon dioxide, which is consistent with the result from the in vitro digestion study. Antioxidant study shows that astaxanthin can be encapsulated in S‐SEDS without the loss of antioxidant activity. Consequently, S‐SEDS can be a promising vehicle in food industry. Practical Applications : Traditionally, liquid‐based delivery systems are prepared using liquid components, which have some disadvantages, such as, complex production process, low active ingredient loading, narrow application range, and lacking of effective evaluation methods. The present study adopts physical adsorption, a gentle and simple process, to prepare the solid self‐emulsifying system. This system combines the advantages of liquid‐based systems and solid dosage forms, which can improve the solubility of poorly solubility active ingredient in intestinal environments, and the high solubility of active ingredient is favor to its absorption. In the present work, the active ingredients solubilization capability of solid formulations is evaluated by in vitro dissolution and digestion studies. It can be seen that over 40% of astaxanthin are released from solid self‐emulsifying systems in 120 min. After the process of digestion, the bioaccessibility reaches 10%. The results of in vitro dissolution and digestion show that after solid adsorption, astaxanthin exhibits delayed release patterns. All the studies demonstrate that solid self‐emulsifying system is an appropriate strategy to improve the bioavailability of astaxanthin. The pseudo ternary phase diagram method is used to screen the optimum composition of liquid self‐emulsification delivery system. Then, this liquid system is converted into solid state using the solid absorbent carrier by simple physical mixing. Abstract : The pseudo ternary phase diagram method is used to screen the optimum composition of liquid self‐emulsification delivery system. Then, this liquid system is converted into solid state using the solid absorbent carrier by simple physical mixing.